Blood lance : a medieval noir - Westerson, Jeri (Westerson, Jeri. Crispin Guest novels., 2012)
Guest, returning home after a late night, sees a body hurtling from the uppermost reaches of the London Bridge. While whispers in the street claim that it was a suicide, Guest is unconvinced. The man was believed to be searching for the Spear of Longinus-- the spear that pierced the side of Christ on the cross-- which is believed to make those who possess it invincible. Geoffrey Chaucer comes to London and is anxious to help Guest find the missing spear... about which he seems to know a bit too much...